(untitled) (Update Dental College Journal, 2014)
Objective: To measure the distribution of TPO-Ab positivity and to observe the effect of thyroid peroxidase positivity on thyroid function during first trimester in normal pregnancy. Method: A cross sectional among 120 subjects were taken in this study and divided into control and study groups. Control group (Group A) consisted of 60 healthy non pregnant women age ranged between 20 to 35 years. Study group (Group B) consisted of 60 normal pregnant women of same age range. Group B was further subdivided into group B1 and group B2according to the level of TPO-Ab. Group B1 consisted of TPO-Ab positive pregnant women and group B2 consisted of TPO- Ab negative pregnant women. Control group was selected from personal contacts and study group from Out Patient Department (OPD) of Obstetrics and Gynecology of Sir Salimullah Medical College and Mitford Hospital. For assessment of thyroid function, serum free thyroxine (FT4), thyroid stimulating hormone (TSH) were measured. Serum FT4, TSH were measured by Enzyme link immunosorbant (ELISA) method. Again, serum TPO-Ab of total study population and hCG of all the pregnant women were measured. Serum TPO-Ab by Micro particle Enzyme Immunoassay (MEIA) method and hCG was estimated by ELISA. Statistical analysis was done by SPSS version 17. Results: In this study, serum FT4 and was significantly (P<0.001) higher and TSH level was significantly (P<0.001) lower in normal pregnant women during 1st trimester in comparison to those of non pregnant women. Again, 18% of pregnant women showed TPO-Ab positivity. However, serum FT4 level was significantly (P<0.001) lower whereas, TSH level was significantly (p<0.001) higher in TPO-Ab positive pregnant women in comparison to those of TPO-Ab negative pregnant women. Conclusion: TPO-Ab positivity increases during 1st trimester of normal pregnancy which decreases the hyper functional state of thyroid hormones. So, thyroid screening should be done routinely during pregnancy. DOI: http://dx.doi.org/10.3329/updcj.v4i1.21160 Update Dent. Coll. j: 2014; 4 (1): 15-20